Implementing Coati Optimization Algorithm in Fuzzy Logic-Based Fractional-Order Tilt-Integral-Derivative Controller for Automatic Generation Control in Multi-Area Multi-Unit Power System - Debashis Sitikantha; Binod Kumar Sahu; Debiprasanna Das (Electrica, 2024)
When there is a mismatch in electrical power produced and the demanded electrical loading in an interconnected electrical power system, it results in deviations in frequencies in the constituent areas and in tie-line power as well. This issue is addressed by automatic generation control which when coupled with intelligent controller leads to fast recovery of the deviations both in tie-line power and frequencies from the assigned ranges associated with each of these areas. This paper is an attempt to utilize fuzzy logic-based fractional-order tilt-integral-derivative (Fuzzy FOTID) controller with gains/parameter optimized using the recent Coati Optimization Algorithm. Comparative studies are undertaken as a part of this work to exhibit the Fuzzy FOTID controller's supremacy over other popular controllers like proportional-integral-derivative, TID, and FOTID.